DEVELOPMENT AND STANDARDIZATION OF URDU APHASIA ASSESSMENT TOOL (UAAT) FOR CLINICAL USE - Faiza Badar; Sajida Naz; Ghulam Saqulain; Muhammad Kashif Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: To develop and validate the Aphasia Assessment Tool in Urdu and determine its clinical accuracy. Methodology: A mixed-methods exploratory study was conducted at Shifa International Hospital from September 2020 to September 2021. The developed tool underwent face validity through peer review. Following changes based on professional feedback, the test was further refined by language experts at the National University of Modern Languages and the Academy of Letters. The pilot study test was then administered to 467 individuals across four provinces in Pakistan, meeting the inclusion criteria. Inter-rater reliability was calculated by having the test scored independently by two therapists. Additionally, UAAT was administered to 70 patients with left middle cerebral artery and 21 patients with right middle cerebral artery infarcts. The sample was also evaluated using the translated version of the Mississippi Aphasia Screening Tool, and scores were compared. A re-administration of the UAAT test after one week on the sample population concluded the study. Results: The Urdu Aphasia Assessment Test revealed a Cronbach’s α=0.89 with significant correlation (p<0.001, r=0.91 with Mississippi Aphasia Screening Tool. The cut-off score quartiles computed at 27.98±25.21 with a mean of 7.50. There was a high inter-item correlations. The factor structure of the scale was assessed with the clinical sample, an exploratory factor analysis was conducted on the 38 items. A principal component analysis was conducted for the one-factor model structure, elucidating 94.00% of the variance. All 38 items exhibited high factor loading on the two-factor structure model, suggesting the retention of all items in the final version of the scale. The one-factor model estimation revealed satisfactory item loadings. Goodness-of-fit model indices.. Conclusion: In conclusion, the Urdu Aphasia Assessment Tool demonstrates reliability and validity for clinically assessing individuals with aphasia in the Urdu language